Examination of accuracy aspect in machining of ZrSiO4p/6063 aluminium MMC using CNC Wire Electrical Discharge Machining. (December 2017) - Garg, Mohinder Pal; Sharma, Anand
Abstract: Wire Electrical Discharge Machining (WEDM) is a deep-rooted non-contact modern machining technique used to manufacture geometrically intricate shapes in hard materials which are difficult to machine using conventional methods. To achieve close dimensional accuracy in WEDM, the output parameter dimensional deviation is an essential response to be controlled during machining. Determination of dimensional deviation for a particular process parameter combination assists the manufacturing planners in setting a wire offset so that the actual (cut) work piece dimensions match the part geometry.This study investigates the dimensional deviation induced by WEDM of ZrSiO4p /6063 Aluminium metal matrix composite (MMC) by using response surface methodology (RSM). The key WEDM input process parameters namely, pulse-on time, pulse-off time, servo voltage and peak current were varied in order to examine their influence on dimensional deviation. Significant process parameters affecting the process are identified by carrying out analysis of variance (ANOVA) technique. To aid in selecting the best combination of input parameters during WEDM of ZrSiO4p /6063 Aluminium MMC the concept of desirability is utilized. Confirmation experiments have been conducted to verify the optimal parameter combinations. Highlights: Aluminium based MMC with improved properties of hardness and tensile strength is fabricated. Exploration of machinability aspects of Al MMC by WEDM. Highly precise dimensional deviation during machining of Al based MMC.